London newsletters collection
Volumes of letters from various persons at the offices of the English ministry at Whitehall Palace addressed chiefly to Sir William Scott relating to such matters as royal travel and itinerary, events in Parliament, military operations in Europe, diplomatic meetings, religious movements, shipping and commercial agreements, and London social life.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Scott, William, -- Sir, -- -1707 -- Correspondence; England and Wales. -- Parliament -- History -- 17th century; Shipping -- Great Britain; Europe -- History, Military -- 1648-1789.; Great Britain -- Commerce; Great Britain -- Foreign relations -- 1660-1714.; Great Britain -- History, Military -- 1603-1714.; Great Britain -- Politics and government -- 1660-1688.; Great Britain -- Religion -- 17th century; London (England) -- Social life and customs -- 17th century